The value-relevance of listed associates: a cross-country investigation. Issue 1 (2nd January 2016) - Badenhorst, Wessel M.; Brümmer, Leon M.; de Wet, Johannes H. v. H.
Abstract : Prior research findings are not conclusive on whether or not equity accounted carrying amounts and disclosed fair values of listed associates are value-relevant in different countries. Using a variety of statistical methods, this study compares the value-relevance of disclosed fair values of listed associates in South Africa, the United Kingdom (UK) and Australia. It finds that value-relevance differs between sample countries, especially when firms in the globalised financial services and mining industries are excluded from the sample, despite increased convergence in accounting standards. This study contributes to the existing literature by directly comparing the cross-country value-relevance of disclosed fair values of listed associates. Findings highlight that generalisation of value-relevance findings across countries and industries should be done with caution.